Factors Influencing Customer Repurchase Intention towards Online Product in Online Shopping Website (B2C E-commerce) " - Pratiwi, Anastasia Galuh; Kusumawati, Nurrani (Journal of Business and Management, 2020)
Abstract. The development of e-commerce business could create an opportunity that has to be generated by e-commerce players, especially B2C E-commerce in order to become successful business by retaining customers through repurchase intention. This research aims to determine the factors influencing customer repurchase intention, to determine the effect of customer satisfaction towards repurchase intention, and to determine the factor that has biggest influence on customer repurchase intention in B2C E-commerce website. The data of this research obtained through in-depth interview to 11 informants who live in Java, aged 15-44 years old, and ever repurchase in B2C E-commerce website. The data that has been collected analyzed by using manual coding. The result shows that price, product quality, sales promotion, and customer satisfaction are the factors influencing online repurchase intention. Furthermore, product quality is the factor that has biggest influence towards online repurchase intention. This research also shows customers tend to repurchase when they feel satisfied with online shopping experience provided by the website. Therefore, satisfaction is animportant key to be considered by B2C E-commerce because it can encourage customer’s intention to repurchase in the website itself.Keywords: B2C E-Commerce, Online Repurchase Intention, Customer Satisfaction, Price, Product Quality, Sales Promotion.